#### Answer

-27

#### Work Step by Step

$\sqrt -9\times\sqrt -81=i\sqrt 9\times i\sqrt 81=i\times3\times i\times9=27i^{2}=27\times-1=-27$
We know that $\sqrt -1=i$, because $i^{2}=-1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-27

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.